Avaliação de blocos de concreto para pavimentação com resíduos de construção e demolição do Município de Juranda/PR - Amadei, Daysa Ione Braga (2011)
With the emergence of sustainability, which was stronger after the massive amount of waste generated due to population explosion of twentieth century and the destruction caused by the 2nd World War, conforms to a scenario in which they aspire alternatives of growth environmentally responsible, in which construction sector comes into focus because of the impact causing both the consumption of resources and the generation of waste. Therefore, the recycling appears as a solution to a sustainable development, considering benefits such as reduced consumption of natural resources, pollution and areas for the sanitary landfill. The interlocking blocks of concrete are a means of using recycled RCD, which besides presenting the various technical advantages inherent to the type of paving, also happens to be a product in favor of environmentally. Thus, this research focuses mainly on the fabrication and evaluation of interlocking blocks of concrete with Construction and Demolition Waste from Juranda City ? PR, partially replacing the natural fine agrregate by recycled fine agrregate in the range of 25% to 50%. It was also proposed an adaptation of the method for dosage of plastic concrete for concrete blocks, because this doesn?t have any method consecrated. After manufacture, the blocks were submitted to tests of resistance to compression, resistance to abrasion and absorption of water. The results showed that the level of 25% substitution reached values above 35 MPa at 28 days, as determined by the NBR 9780 (1987), and provide satisfactory values in the other parameters not covered by standard. The indices of 30% and 35%, although not reach the resistance determined by Brazilian standard, obtained satisfactory results to be emploued in places requiring low demands of traffic.